Social identity and economic inequalities - Yilmaz, Ensar; Bagce, Sinem (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2022)
Neoclassical economists explain social phenomena in the decision-making process with the rational and prudent agent, seeking the highest amount of personal utility with her idiosyncratic preferences. However, atomistic choices and preferences cannot explain the phenomena, such as unequal living conditions and discrimination in labor. The agent, as a human being, is always in interaction with the social environment. Social identity is one of the areas in which the social environment is influential. Social identities are associated with social inequalities, directed by some practices, attitudes and institutions that negatively affect the life prospects of social groups of different identities. Therefore, economists need the social unifying analytical concepts, such as social identity, to comprehend the inequalities and related issues, such as redistribution policies in societies.
Keywords: Identity; inequality; ethnicity; gender; economics; STATISTICAL DISCRIMINATION; UNITED-STATES; IMMIGRANTS; REDISTRIBUTION; EMPLOYMENT; EARNINGS; DEMAND; RACISM; WOMEN; MODEL; Ethnic Studies